The product, the mind and the heart of crowdfunding: the effect of signals on technology projects. (2017) - Ceballos, Ruben; Hou, Wanrong; Levitas, Edward; Price, Sherrell Mitchell
Signalling theory is useful for describing behaviour when two individuals or organisations have access to different information. The current research intends to explain how technology entrepreneurs can successfully utilise this theory to secure crowdfunding. Specifically, we predict that the innovativeness of a project, the skills, abilities, honesty and kindness of individual workers, can positively affect crowdfunding achievement. We also hypothesise and test that positive emotional characteristics in the workplace can strengthen the relationship between products usefulness and funding success. Data was collected from Kickstarter platform to test our theory. Our analyses show that specific individual skill (entrepreneurs' industry experience) negatively influences their funding success, but entrepreneur's personal characteristics (previous funding experience and frequent updates) are positively related to crowdfunding achievement. In addition, the level of education positively influences the relationship between innovation and funding success. Social factors dominate crowdfunding more than economic soundness. Crowdfunding can be used to fund innovative and traditional projects.